Analisis Perbedaan Jumlah Nyamuk Aedes sp. yang Terperangkap pada Ovitrap Standar dan Ovitrap Bambu - Askrening; Reni Yunus; Susilawati (Health Information : Jurnal Penelitian, 2020)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that occurs because of dengue virus infection, which is carried by the vector Aedes sp. Kendari City is one of the dengue-endemic areas in Southeast Sulawesi Province. Some control programs of Aedes sp. so far less successful because it places more emphasis on fogging for adult mosquitoes. There are methods of controlling Aedes sp. without insecticide which has so far reduced vector density in some countries, namely the use of egg traps (ovitrap). This study aims to determine differences in the number of eggs trapped in standard ovitrap and bamboo ovitrap. This research is an observational study with a cross-sectional method. The results showed that the p-value 0.6168 which meant that there was no difference between mosquito eggs trapped in standard ovitrap and bamboo ovitrap.